Seroprevalence of SARS-CoV-2 antibodies, associated epidemiological factors and antibody kinetics among healthcare workers in Connecticut. (August 2021) - Papasavas, P.; Olugbile, S.; Wu, U.; Robinson, K.; Roberts, A.L.; O'Sullivan, D.M.; McLaughlin, T.; Mather, J.F.; Steinberg, A.C.; Orlando, R.; Kumar, A.
Summary: Background: Healthcare workers (HCWs) are at the front line of the ongoing coronavirus 2019 (COVID-19) pandemic. Comprehensive evaluation of the seroprevalence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) among HCWs in a large healthcare system could help to identify the impact of epidemiological factors and the presence of symptoms on the immune response to the infection over time. Aim: To determine the seroprevalence of SARS-CoV-2-specific antibodies among HCWs, identify associated epidemiological factors and study antibody kinetics. Methods: A longitudinal evaluation of the seroprevalence and epidemiology of SARS-CoV-2-specific antibodies was undertaken in approximately 30, 000 HCWs in the largest healthcare system in Connecticut, USA. Findings: At baseline, the prevalence of SARS-CoV-2 antibody among 6863 HCWs was 6.3% [95% confidence interval (CI) 5.7–6.9%], and was highest among patient care support (16.7%), medical assistants (9.1%) and nurses (8.2%), and lower for physicians (3.8%) and advanced practice providers (4.5%). Seroprevalence was significantly higher among African Americans [odds ratio (OR) 3.26 compared with Caucasians, 95% CI 1.77–5.99], in participants with at least one symptom of COVID-19 (OR 3.00, 95% CI 1.92–4.68), and in those reporting prior quarantine (OR 3.83, 95% CI 2.57–5.70). No symptoms were reported in 24% of seropositive participants. Among the 47% of participants who returned for a follow-up serological test, the seroreversion rate was 39.5% and the seroconversion rate was 2.2%. The incidence of re-infection in the seropositive group was zero. Conclusion: Although there is a decline in the immunoglobulin G antibody signal over time, 60.5% of seropositive HCWs had maintained their seroconversion status after a median of 5.5 months.